Monsters : evil beings, mythical beasts, and all manner of imaginary terrors - Gilmore, David D., 1943- (University of Pennsylvania Press, 2003)
Like so many other eternal adolescents, I am fascinated by imaginary monsters- especially the luscious ghouls and extraterrestrials in sci-fi literature and Hollywood films. They always inspired both dread and attraction in me, or perhaps empathy is a better word. So, given this morbid interest, the present book may represent a coming to grips with a juvenile obsession that has endured well into middle age. The appeal of monsters reaches a peak in childhood, when all prudent boys and girls check under their beds at night for demons, but it lingers well into adulthood. In those who are seriously weird-a category I admit belonging to-it evolves into a luxurious repertory of fantasies, anxieties, and phobias.